MARFE movement and density fluctuations after deuterium pellet injections in H-mode plasmas on EAST tokamak. (1st May 2022) - Hou, Jilei; Chen, Yue; Zuo, Guizhong; Hu, Jiansheng; Mao, Songtao; Yuan, Xiaolin; Huang, Jia; Wu, Mingfu; Xu, Liqing; Zhao, Hailin; Yuan, Jingsheng; Wang, Shouxin; et al.
Abstract: The multifaceted asymmetric radiation from the edge (MARFE), which is generally considered to be the result of a radiation thermal instability in the edge and usually occurs in high density operation, has been first observed to move up and down along the poloidal cross-section due to edge cooling after cryogenic deuterium pellet injections in EAST tokamak with tungsten divertor. A maximum electron density of 0.84 × n GW has been obtained using continuous cryogenic pellet fueling. In the meantime, MARFEs, initially located near the divertors of EAST, moves to the inner wall on high field side after each pellet injection. This movement should be attributed to the asymmetry of the power flow to the two sides of the MARFE after pellet injections. Accompanied with MARFE movement, two kinds of strong density fluctuations have been observed. The ones with continuous and regular frequency spectrum, which does not cause a reduction of main plasma density, are confirmed to be induced by MARFE. The others, appearing with magnetic fluctuations, have been determined to be induced by the m / n = 2/1 magnetohydrodynamic activities after pellet injections. All the investigations in this paper will be meaningful for the steady high density operation of future fusion reactors, such as ITER.